2005
DOI: 10.1111/j.1365-2109.2005.01336.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of incubation temperature on development and yolk sac conversion efficiencies of spotted wolffish (Anarhichas minor Olafsen) embryos until hatch

Abstract: Two egg batches of spotted wol⁄sh, Anarhichas minor Olafsen, were incubated at 4, 6 and 8 1C. Embryo samples were ¢xed and compared on each100th daydegree until hatching (up to 1000 daydegrees). Embryos, yolk sacs and chorions were dissected and the sizes, wet and dry weights were recorded separately. Comparisons of gross morphologies and measured parameters showed increasing and generally signi¢cant di¡erences with time between the incubation temperatures. Lower temperatures produced longer and more di¡erenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…This is consistent with the differential consumption of yolk observed in Anarhichas minor (Sund & Falk-Petersen, 2005), where decreased consumption occurred at higher temperature and thus the embryos had more yolk at hatching and were more bent over the yolk sac. Sund & Falk-Petersen (2005) and Peterson et al (2004) also observed in Anarhichas minor and Gadus morhua that embryos incubated at lower temperature hatched with larger length. Furthermore, water temperature directs the sexual differentiation process in the pejerrey Odontesthes bonariensis (Valenciennes) and affects larval condition and growth rate (Strüssmann & Patiño, 1995;Ito et al, 2005;Chalde et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is consistent with the differential consumption of yolk observed in Anarhichas minor (Sund & Falk-Petersen, 2005), where decreased consumption occurred at higher temperature and thus the embryos had more yolk at hatching and were more bent over the yolk sac. Sund & Falk-Petersen (2005) and Peterson et al (2004) also observed in Anarhichas minor and Gadus morhua that embryos incubated at lower temperature hatched with larger length. Furthermore, water temperature directs the sexual differentiation process in the pejerrey Odontesthes bonariensis (Valenciennes) and affects larval condition and growth rate (Strüssmann & Patiño, 1995;Ito et al, 2005;Chalde et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…Probably, the size of the yolk sac and the bending of the embryo after hatching will be major factors operating on the beginning of exogenous feeding (Battini et al, 1995). This is consistent with the differential consumption of yolk observed in Anarhichas minor (Sund & Falk-Petersen, 2005), where decreased consumption occurred at higher temperature and thus the embryos had more yolk at hatching and were more bent over the yolk sac. Sund & Falk-Petersen (2005) and Peterson et al (2004) also observed in Anarhichas minor and Gadus morhua that embryos incubated at lower temperature hatched with larger length.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, warm temperature accelerates chorion rupture (Nwosu & Holzorner 2000) and consequent hatching. However, very high temperatures can cause morphological alterations, thereby decreasing larvae survival (Sund & Falk‐Petersen 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Higher water temperatures, within certain limits, accelerate the process of chorion rupturing and, consequently, hatching (Borçato et al, 2004;Nwosu & Holzorner, 2001). Water temperature during egg incubation has been considered important in the speed of embryonic development and survival rate (Hansen & Falk-Petersen, 2002), but very high temperatures can cause abnormalities and decreased larval survival rates (Sund & Falk-Petersen, 2005). The eggs of M. elongatus in the present study were kept in incubators with a constant water flow at 23°C with eggs hatching at 24 hr 50 min.…”
Section: Discussionmentioning
confidence: 99%